Memahami Hukum Islam melalui Hadis - Harjana, Dwi; Talli, Abdul Halim; Ridwan, Saleh (Shar-E : Jurnal Kajian Ekonomi Hukum Syariah, 2025)
This study examines the existence of hadith as the second source of Islamic law after the Qur’an, as well as the methods employed to interpret and implement it in the formation of Islamic legal rulings. Hadith serves as an explanation of Qur’anic verses, a source of new legal rulings, and a guide for Muslim daily life. The research combines library study and field observation, employing the maqāṣid al-syarī‘ah approach to analyze the principles, methods, and both textual and contextual approaches in understanding hadith. Findings reveal that a comprehensive understanding of hadith requires verification of the chain of transmission, analysis of the text, and consideration of historical and social contexts. Accordingly, hadith not only reinforces its position as a source of Islamic law but also contributes to the development of relevant, applicable, and contemporary-oriented legal solutions.